2000
DOI: 10.1046/j.1365-2648.2000.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Drawing up and administering intramuscular injections: a review of the literature

Abstract: Drawing up and administering intramuscular injections: a review of the literature Intramuscular (IM) injections have been an integral part of drug administration in nursing practice for almost half a century. However, there are some conflicting practices which warrant investigation to determine their effectiveness in this aspect of patient care. To this end, this paper presents the results of a literature review which was carried out in order to establish current understanding of present day knowledge, procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 35 publications
4
126
1
4
Order By: Relevance
“…This dose is higher than that recommended by the National Institutes of Health in humans (0.17 mg/kg), but has been found to be the dosage in sheep that consistently produces preterm fetal lung maturation (Moss et al, 2001). This is also the highest dose level that can be investigated because it is associated with an injection size of 4 to 6 ml, which is the maximum recommended intramuscular administration volume (Rodger and King, 2000). The use of a high dose is necessary to capture the low-level betamethasone release that could occur from the acetate prodrug.…”
mentioning
confidence: 96%
“…This dose is higher than that recommended by the National Institutes of Health in humans (0.17 mg/kg), but has been found to be the dosage in sheep that consistently produces preterm fetal lung maturation (Moss et al, 2001). This is also the highest dose level that can be investigated because it is associated with an injection size of 4 to 6 ml, which is the maximum recommended intramuscular administration volume (Rodger and King, 2000). The use of a high dose is necessary to capture the low-level betamethasone release that could occur from the acetate prodrug.…”
mentioning
confidence: 96%
“…Excessive proximal site could lead to bursa injection, while excessive distal site could lead to nerve damage or injection into vessels [11,12]. However, cadaver studies indicated that the distance from the tip of the acromion to the axillary nerve had as wide a range of 4-8 cm, with an average distance of 5-6 cm.…”
Section: Deltoid Intramuscular Injection Techniquementioning
confidence: 99%
“…Additionally, the number and volume of injections should be limited due to its small muscle mass. The suggested maximum injection volume at a deltoid site is 1-2 ml [10,12].…”
Section: Deltoid Intramuscular Injection Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] However, with this method there is no agreement on the position of injection, with variable distances below the acromion being recommended, measured as centimeters or finger breadths/ widths. Another technique, also with strong nursing support, [17][18][19][20][21][22] involves location of the acromion and a line drawn laterally across the deltoid muscle from the apex of the anterior axilla. All authors place the apex of a triangle on the latter line, with some authors 18,21 placing the base of the triangle on the acromion and others [17][18][19][20]22 placing it two to three finger breadths below the acromion.…”
Section: Introductionmentioning
confidence: 99%